(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
With the help of our own non-stationary model, the defrosting times of frozed beech logs with a diameter of 0.4 m, initial temperature of −10o C, −20o C, −30o C, and moisture content of 0.6 kg∙kg-1 were determined at water temperatures in the boiling pit equal to 80o C. Using the determined logs’ defrosting durations, the change in energy required for the entire plasticization process and that for each of the 5 components of the pit’s thermal balance was calculated. Computer simulations were performed for a well-insulated concrete pit with working volume of 20 m3 and degree of filling with logs f equal to 25%, 50%, and 75%. It was found that at f = 75% the total energy consumption of the pit increases from 163.6 kWh.m-3 to 177.6 kWh∙m-3 when the initial temperature of the logs decreases from −10o C to −30o C. The thermal efficiencyof the studied pit decreases almost proportional to the decreasing of f, mainly due to the increase in the specific energy required to heat the water in the pit.